Amelioration of experimental autoimmune encephalomyelitis by gemfibrozil in mice via PPARβ/δ: implications for multiple sclerosis - Mondal, Susanta; Sheinin, Monica; Rangasamy, Suresh B.; Pahan, Kalipada (Frontiers in Cellular Neuroscience, 2024)
It is important to describe effective and non-toxic therapies for multiple sclerosis (MS), an autoimmune demyelinating disease. Experimental autoimmune encephalomyelitis (EAE) is an immune-mediated inflammatory disease that serves as a model for MS. Earlier we and others have been shown that, gemfibrozil, a lipid-lowering drug, exhibits therapeutic efficacy in EAE. However, the underlying mechanism was poorly understood. Although gemfibrozil is a known ligand of peroxisome proliferator-activated receptor α (PPARα), here, we established that oral administration of gemfibrozil preserved the integrity of blood-brain barrier (BBB) and blood-spinal cord barrier (BSB), decreased the infiltration of mononuclear cells into the CNS and inhibited the disease process of EAE in both wild type and PPARα -/-mice. On the other hand, oral gemfibrozil was found ineffective in maintaining the integrity of BBB/BSB, suppressing inflammatory infiltration and reducing the disease process of EAE in mice lacking PPARβ (formerly PPARδ), indicating an important role of PPARβ/δ, but not PPARα, in gemfibrozil-mediated preservation of BBB/BSB and protection of EAE. Regulatory T cells (Tregs) play a critical role in the disease process of EAE/MS and we also demonstrated that oral gemfibrozil protected Tregs in WT and PPARα -/-EAE mice, but not PPARβ -/-EAE mice. Taken together, our findings suggest that gemfibrozil, a known ligand of PPARα, preserves the integrity of BBB/BSB, enriches Tregs, and inhibits the disease process of EAE via PPARβ, but not PPARα.